Experimental Study on Reactive Powder Concrete under Flexural Loading - P, Jeganmurugan; Senthil Kumar G V, Rakesh; M, Sivasharmina; S, Sowmiya; M, Vasanthan (International Journal of Engineering and Technology, 2018)
Reactive powder concrete (RPC) is ultra high strength with advanced mechanical properties. Reactive powder concrete is a concrete without coarse aggregate, contains cement, silica fume, quartz sand, quartz powder, super plasticizer, steel fibre and polypropylene fibre with very low water cement ratio under normal curing condition. RPC has been produce with high compressive strength ranging from upto 800 MPa with high flexural strength up to 50 MPa and in some cases provided with absences of steel reinforcement. Mix proportions of RPC were found by trial and error method, the concrete cubes of size 100mmx100mmx100mm were cast for find compressive strength of NRPC at 7days. Concrete cubes and cylinders of sizes 100mmx100mmx100mm and 100mmx150mm have to be cast for finding compressive strength and split tensile strength at 28 days. Flexural strength of NRPC and MRPC will be find out by casting prism of size 500mmx 100mmx 100 mm. The optimum mix proportion has to be finalized by comparing the results of all concrete specimens. Compressive strength test results shows that addition of silica fume upto 0.22% will increase the compressive strength of reactive powder concrete. Â Â